Clinical Practice Guidelines for Rehabilitation of Patients in critical Condition. - José Gómez Cruz (Medisur, 2009)
Clinical Practice Guidelines for Rehabilitation of Patients in critical Condition. It is the integral, multidisciplinary rehabilitation, including the prevention in advance of all possible sequels caused by the disease or lesion. Understood as a group of non invasive, appropriate and tolerable procedures meeting the individual needs and aimed at preserving the indemnity of structures and functions that have not been involved in the disease. We list its principles and intervention stages, instruments and international evaluation scales used for assessment and treatment of patients in critical condition and it therapeutic alternatives. It includes assessment guidelines focused on the most important aspects to be accomplished.